Ab initio study of a cubic perovskite: Structural, electronic, optical and electrical properties of native, lanthanum- and antimony-doped barium tin oxide. (April 2015) - Slassi, Amine
Abstract: We use density functional theory and semiclassical Boltzmann equation to investigate the structural, electronic, optical and electrical properties of native, lanthanum- and antimony-doped barium tin oxide. We find that lanthanum dopant introduces shallow donor states close to the bottom of the conduction band, whereas antimony dopant introduces deep states inside the band gap. The transmittance and electrical conductivity for lanthanum-doped barium tin oxide are significantly enhanced offering a good transparent conducting oxide, while are not as desired for antimony-doped barium tin oxide. On the other hand, the antimony-dopant enhances the visible light absorption of barium tin oxide, which might be useful for other applications as photocatalysts.